Analisis Penetapan Tarif Dasar PAMSIMAS Desa Sungai Raja Berdasarkan Teori Full Cost Recovery Dalam Persfektif Ekonomi Islam - Melisa Syafitri Amalia; Isnaini Harahap; Wahyu Syarvina (VISA: Journal of Vision and Ideas, 2023)
This study aims to determine and understand the setting of PAMSIMAS tariffs in Sungai Raja Village based on the Full Cost Recovery theory and to understand and understand the Islamic Economics review of the setting of PAMSIMAS tariffs in Sungai Raja Village. The research methodology used is qualitative with descriptive method. The object of this research is PAMSIMAS Sungai Raja Village. Sources of data used in this study are primary data and secondary data. Primary data in the form of interviews, documentation and secondary data in the form of regulations and laws relating to the determination of drinking water tariffs, PAMSIMAS financial reports, number of customers, amount of water sold, data on water sources, installed capacity, sold capacity. Based on data analysis. The results of this study stated that adopting the regulation of the minister of home affairs number 21 of 2021 regarding the calculation and determination of drinking water tariffs, it was stated that based on the theory of Full Cost Recovery (full cost recovery) by formulating a basic cost, a basic tariff of Rp. 6,721/m3 while the tariff that is still in effect at Sungai Raja Village PAMSIMAS of Rp. 1500/m3 has not met the tariff with a full cost revovery mechanism. Based on the perspective of Islamic Economics, it is still contrary to Islam because the determination of the selling tariff for PAMSIMAS water is still detrimental to both parties (seller and buyer). Keywords: Full Cost Recovery, PAMSIMAS, Tariff Setting, Islamic Economic Perspective